The Role of Trust in Argumentation - Dutilh Novaes, Catarina (Informal Logic)

(untitled) (Informal Logic, 2020)
Argumentation is important for sharing knowledge and information. Given that the receiver of an argument purportedly engages first and foremost with its content, one might expect trust to play a negligible epistemic role, as opposed to its crucial role in testimony. I argue on the contrary that trust plays a fundamental role in argumentative engagement. I present a realistic social epistemological account of argumentation inspired by social exchange theory. Here, argumentation is a form of epistemic exchange. I illustrate my argument with two real-life examples: vaccination hesitancy, and the undermining of the credibility of traditional sources of information by authoritarian politicians.